Association between PCSK9 inhibitors and acute kidney injury: a pharmacovigilance study - Liu, Hailing (Frontiers in Pharmacology, 2024)
Background PCSK9 inhibitors are a novel class of lipid-lowering medications, and numerous clinical studies have confirmed their significant role in improving the progression of chronic kidney disease. However, recent case reports have indicated new evidence regarding their association with acute kidney injury (AKI), with some patients experiencing acute tubular injury after PCSK9 inhibitors use. Objectives To clarify the relationship between PCSK9 inhibitors and AKI, we conducted a pharmacovigilance study. Methods Using the Food and Drug Administration Adverse Event Reporting System (FAERS) database from the third quarter of 2015 to the fourth quarter of 2022, a disproportionality analysis was employed to identify adverse events suggestive of AKI after PCSK9 inhibitors use. The drugs of interest included evolocumab and alirocumab. Results A total of 144,341 adverse event reports related to PCSK9 inhibitors were analyzed, among which 444 cases were suspected of AKI for evolocumab, and 172 cases for alirocumab. Evolocumab had a greater impact on AKI in males (ROR 1.4, 95% CI 1.54-1.69). The ROR and 95% CI for evolocumab and Alirocumab were 0.13 (0.12-0.14) and 0.26 (0.23-0.30) respectively. Further analysis of AKI associated with the concomitant use of PCSK9 inhibitors with cephalosporins, furosemide, torsemide, pantoprazole, omeprazole, and esomeprazole revealed ROR and 95% CI of 0.38 (0.23-0.62), 0.38 (0.31-0.48), 0.18 (0.08-0.38), 0.23 (0.17-0.29), 0.20 (0.16-0.26), and 0.14 (0.10-0.20) respectively. Conclusions Through the FAERS database, we analyzed the clinical characteristics of AKI associated with PCSK9 inhibitors, exploring its risks. Our findings suggest that PCSK9 inhibitors might have a potential protective effect against AKI and exhibit similar effects when co-administered with other nephrotoxic drugs.